Caregiver responsiveness as a mechanism to improve social communication in toddlers: Secondary analysis of a randomized controlled trial. Issue 2 (20th November 2021) - Davis, Paige Huguely; Elsayed, Heba; Crais, Elizabeth R.; Watson, Linda R.; Grzadzinski, Rebecca
Abstract: Early intensive behavioral interventions (EIBI) for children at elevated likelihood for a later diagnosis of autism spectrum disorder (EL‐ASD), are often delivered through parent‐mediated models. An area of current exploration is whether changes in caregiver behaviors are a mechanism through which to improve and track child behaviors in these interventions. Toddlers and their caregivers participated in an intervention trial (randomized controlled trial) and were randomized to either a parent‐mediated intervention (adapted responsive teaching; ART) or a control condition (referral to early intervention and monitoring; REIM). Changes in toddler social communication (SC) behaviors and characteristics of caregiver responsiveness (CR) were quantified over 8 months. Analyses were conducted to assess whether changes in CR mediated the relation between group (ART vs. REIM) and changes in child SC. Results of the current study indicated that caregivers who participated in a parent‐mediated intervention improved in three domains of CR (contingent verbal sensitivity, responsivity, affect). CR was also found to be a mechanism through which children's SC skills improved. This work provides evidence that qualities of CR serve as mechanisms through which to improve and monitor child behaviors over the course of EIBIs. These results may lead to novel intervention targets, methods for tracking change, and tailored treatment planning for toddlers with EL‐ASD. The data used in this study comes from a clinical trial that was prospectively registered with the Registry of Efficacy and Effectiveness Studies (Registry ID: 316.1v1). Lay Summary: Interventions for toddlers with high likelihood for a later diagnosis of autism often include the caregiver as an active participant in the intervention. In this study, we aimed to understand qualities of caregiver responsiveness (CR) that facilitate improvements in child behaviors during intervention. Results show that increasing verbal CR and affect are ways to improve child social skills over the course of intervention.